People to People Diplomacy melalui Program Ausbildung: Melihat Peran Diaspora Indonesia di Jerman terhadap Penguatan Bilateral - Syahnedy, Dara Bunga; Aditiany, Savitri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study explores how Indonesian diaspora in Germany, particularly those involved in the Ausbildung vocational program, contribute to bilateral relations through people to people diplomacy. While Indonesia–Germany relations have conventionally been built through formal channels, the increasing mobility of skilled workers opens new opportunities for grassroots diplomacy. This research aims to analyze the role of diaspora as informal agents of soft power who bridge cultural understanding and foster social trust across borders. Employing a qualitative descriptive- analytical method, the study draws from secondary data sources, including policy documents, digital media content, and diaspora community publications. Conceptually, the research combines the frameworks of people-to-people diplomacy and soft power to understand non-state actor contributions to diplomacy. The findings indicate that diaspora not only act as cultural representatives but also influence bilateral dynamics through digital narratives, workplace interaction, and community engagement. Their presence shapes a favorable image of Indonesia and supports long-term cooperation in vocational education and labor partnerships. This study suggests that Indonesia’s foreign policy should strategically integrate diaspora communities into its public diplomacy efforts, particularly by supporting grassroots initiatives and digital cultural representation to strengthen bilateral ties through informal yet impactful means.